2011
DOI: 10.1016/j.pep.2010.12.011
|View full text |Cite
|
Sign up to set email alerts
|

The epitope for the polyol-responsive monoclonal antibody 8RB13 is in the flap-domain of the beta-subunit of bacterial RNA polymerase and can be used as an epitope tag for immunoaffinity chromatography

Abstract: Polyol-responsive monoclonal antibodies (PR-mAbs) are useful for the purification of proteins in an easy, one step immunoaffinity step. These antibodies allow for gentle purification of proteins and protein complexes using a combination of a low molecular weight polyhydroxylated compound (polyol) and a nonchaotrophic salt in the eluting buffer. mAb 8RB13 has been characterized as one of these PR-mAbs and has been used to purify RNA polymerase from 5 species of bacteria. Here the epitope for 8RB13 has been iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 13 publications
2
13
0
Order By: Relevance
“…The plasmid construct containing green fluorescent (GFP) with a C-terminal epitope tag consisting of the amino acids PEEKLLRAIFGEKAS (etGFP) and the expression of soluble protein by growth at 26°C in E. coli in the presence of an over-expressed GroEL and GroES system has been described [16]. Because the epitope tag was derived from the β-subunit of RNA polymerase, the bacterial lysate was adjusted to 300 mM NaCl and polyethyleneimine was added to a final concentration of 0.3%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The plasmid construct containing green fluorescent (GFP) with a C-terminal epitope tag consisting of the amino acids PEEKLLRAIFGEKAS (etGFP) and the expression of soluble protein by growth at 26°C in E. coli in the presence of an over-expressed GroEL and GroES system has been described [16]. Because the epitope tag was derived from the β-subunit of RNA polymerase, the bacterial lysate was adjusted to 300 mM NaCl and polyethyleneimine was added to a final concentration of 0.3%.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work [16] demonstrated that the strength of the mAb 8RB13/epitope tag interaction could be weakened by increasing AS concentration, such that weakly bound complexes could be artificially generated in a predictable and repeatable manner. IP of etGFP was performed using both IFAST and washing-based protocols as previously described, except that the washing and binding solutions were replaced by AS buffers (50 mM Tris-HCl and 0.1 mM EDTA, pH 7.9) containing 0 to 250 mM AS and 20% propylene glycol.…”
Section: Methodsmentioning
confidence: 99%
“…S. aureus core RNAp was purified from exponentially growing S. aureus strain NCTC8325 cells (harvested at OD 600 ∼ 0.5) by immunoaffinity chromatography on a homemade column packed with 2 ml of resin containing the polyol-responsive monoclonal antibody 8BR13 (Neoclone). 43 The procedure used for immunoaffinity chromatography with 8RB13 followed the protocol described by Thompson and Burgess. 44 Briefly, the cell pellet was resuspended in lysis buffer [10 mM Tris-Cl (pH 7.5), 15 mM MgCl 2 , 50 mM KCl, 5 mM ethylenediaminetetraacetic acid (EDTA), 10 mM 2-mercaptoethanol and 1 tablet of protease inhibitors (Roche) per 100 ml of lysis buffer] and mechanically lysed using a French Press system.…”
Section: Methodsmentioning
confidence: 99%
“…ELISA-elution assay was performed as described previously [12]. Here, the rhPA milk whey was immobilized, cross-reacting with the primary antibody (supernatant of positive hybridoma cells) for 2 h at 37 °C.…”
Section: Screening For Pr-mabsmentioning
confidence: 99%
“…According to Table1, three hybridoma strains were superior in terms of producing PR-mAbs, as follows: C1, C4, and C8. The values of D-OD reached 5 0 % [10,12].…”
Section: Screening Of Polyol-responsive Monoclonal Antibodymentioning
confidence: 99%